Neighbourhoods as relational places for people living with dementia. (May 2020) - Clark, Andrew; Campbell, Sarah; Keady, John; Kullberg, Agneta; Manji, Kainde; Rummery, Kirstein; Ward, Richard
Abstract: An increase in the number of people living independently with dementia across the developed world has focused attention on the relevance of neighbourhood spaces for enabling or facilitating good social health and wellbeing. Taking the lived experiences and daily realities of people living with dementia as a starting point, this paper contributes new understanding about the relevance of local places for supporting those living with the condition. The paper outlines findings from a study of the neighbourhood experiences, drawing on new data collected from a creative blend of qualitatively-driven mixed methods with people living in a diverse array of settings across three international settings. The paper details some of the implications of neighbourhoods as sites of social connection based on material from 67 people living with dementia and 62 nominated care-partners. It demonstrates how neighbourhoods are experienced as relational places and considers how people living with dementia contribute to the production of such places through engagement and interaction, and in ways that may be beneficial to social health. We contend that research has rarely focused on the subjective, experiential and 'everyday' social practices that contextualise neighbourhood life for people living with dementia. In doing so, the paper extends empirical and conceptual understanding of the relevance of neighbourhoods as relational sites of connection, interaction, and social engagement for people living with dementia. Highlights: Presents new data from 129 individuals; 67 living with dementia and 62 care-partners. Neighbourhoods are sites of social interaction, connection and engagement. Neighbourhoods are important sites of support for people living with dementia. People living with dementia can be socially active in neighbourhood locations. Neighbourhoods should be understood as relational places.